Infecção por Rickettsia rickettsii em cães, equídeos e carrapatos de áreas de ocorrência de febre maculosa brasileira na região central do Estado do Espírito Santo - Correa, Gabriel Nunes de Sales (2015)
The State of Espírito Santo has a history of cases of Brazilian Spotted Fever (BSF) since the end of the eighties, registered for the first time in the region of Colatina. The municipality is located in the Central region of the State. Since that, the cases of BSF continued to be reported, with the occurrence of almost 60% of them at the Central region of Espírito Santo. This research aimed to study the Brazilian Spotted Fever’s epidemiology in endemic areas from the Central region of the State of Espírito Santo as well as to identify the tick species with the higher infection rate by Rickettsia through Polymerase Chain Reaction (PCR) and to determine the positivity rate in dogs and horses through the Indirect Immunefluorescence Reaction (IFI). The municipalities visited were all those who, between the years of 2007 and 2014, had confirmed cases of BSF: Baixo Guandu, Colatina, Mantenópolis, Pancas, São Gabriel da Palha, São Roque do Canaã and Vila Valério. It was taken as the control area the municipality of São Domingos do Norte where there are not reports of cases of Brazilian Spotted Fever so far. The collections occurred in the suspected infection sites (SIS) between the months of November 2013 and November 2014, on a monthly basis. In total, blood samples were collected for serology from 72 dogs (1,38% of IFI positivity) and 107 horses (4,63% of IFI positivity), totaling 179 amplifying hosts. The ticks species observed, among the 2.640 specimens collected, were Amblyomma sculptum (72,65%), A. dubitatum (0,41%), Rhipicephallus (Boophillus) microplus (2,23%), R. sanguineus (4,01%) and Anocentor nitens (20,68%). From that number, only a tick (0,0038%) identified as A. sculptum disclosed a positive result in PCR. All municipalities visited, including the control area, had the presence of capybara’s (Hydrochaeris hydrochaeris). As much as the largest quantity of collections has 20 been represented by the main tick species involved in the transmission of the FMB in the Southeast of Brazil, A.sculptum, the PCR results were low as well, were those of serological evaluation by IFI for detection of anti-Rickettsia rickettsii antibodies in the amplifying hosts In view of the history of the region evaluated in this study, besides the low amount of results observed in the laboratory tests, it can be concluded that, possibly, the BSF’s cycle in the Central region of the Espírito Santo is maintained, in large part, by wild amplifying hosts, mainly the capybaras. The low results, as the PCR, as the IFI, may be due to the lack of research from other rickettsias’ species of medical importance. It is of paramount importance an active surveillance in these areas, including the municipality of São Domingos do Norte (control area: positive result at IFI in a horse). The performance of new surveys, both acarological as serological, focused on the amplifying hosts and including others rickettsias’ species, will allow a better understanding of as the epidemiology, as the ecology, of BSF in the Central region of the State of Espírito Santo.